MOVIE TICKETS SALES ADMINISTRATIVE APPLICATIONS 21CINEPLEX MEGARIA USING MICROSOFT VISUAL BASIC 6.0 AND ADOBE PHOTOSHOP CS2 - Elis soraya; Elly Agustina. J, Skom, MMSI Elly Agustina. J, Skom, MMSI (Jurnal Sistem Informasi, 2006)
Ticket sales are done in recent years are still using the manual way by crossing a box containing a number of places when the place was filled, and considering the limited counter worker performance, reports sales are made on the day were not reported in detail. Imbalances resulting report was received by the sales manager with daily official reports.